Ecological Spectrums of Heterotrophic Flagellates (Protista) in Water Bodies of Ukrainian Polissya Area - Shevchuk, S.Yu.; Dovgal, I.V. (Вестник зоологии, 2010)
Dependence of 26 heterotrophic flagellate species development in central part of Ukrainian Polissya area from operating pH and concentrations of dissolved organic matter and oxygen in the waters is considered. Narrowing of existence spectrums in certain types of water body characteristic for some species of heterotrophic flagellates is stated; this peculiarity is strongly expressed in the bogs where specific complex of hydrochemical conditions to have a place.